Casona Epoca del Caucho - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo la fachada de una casona del periodo del caucho con diseños de azulejos que funciona como el local del canal de radio y television T.V.S.
ENGLISH: We observed the facade of a rubber-period house with tile designs that functions as the premises of the T.V.S. radio and television channel.

SPANISH: Se observo la fachada de una casona del periodo del caucho con diseños de azulejos que funciona como el local del canal de radio y television T.V.S.
ENGLISH: We observed the facade of a rubber-period house with tile designs that functions as the premises of the T.V.S. radio and television channel.
Casona Epoca del Caucho
Keywords: Iquitos (Perú)|~|Radio and Television|~|Commercial Radio Broadcasting and Television and Radio Production of Peru|~|Radio and Television|~|Iquitos (Perú)|~|Radio y televisión|~|Perú|~|Radiodifusión Comercial y la Producción Televisiva y Radial del Perú|~|Radio y Televisión|~|Iquitos (Perú)|~|Radio and Television|~|Peru|~|Commercial Radio Broadcasting and Television and Radio Production of Peru|~|Radio and Television